THE IMPACT OF CONTENT MARKETING AND CUSTOMER REVIEWS ON ONLINE PURCHASE DECISIONS AMONG GEN Z IN TOKOPEDIA - Kuswiyono, Arini Novandalina; Arifin, Samsul (Magister Manajemen of Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study investigates the influence of content marketing and customer reviews on purchase decisions among Generation Z users in Bangsri District using the Tokopedia e-commerce platform. A quantitative approach was employed, with data collected through an online questionnaire and analyzed using SEM-PLS. The findings reveal that content marketing significantly affects both customer reviews and purchase decisions, while customer reviews also have a significant direct effect on purchase decisions. Moreover, customer reviews mediate the relationship between content marketing and purchase decisions. These results highlight the importance of digital content strategy and customer engagement in shaping online buying behavior. The study contributes theoretically by integrating three key digital marketing variables and offers practical insights for e-commerce marketers targeting Gen Z consumers.